Epidemiological Serosurvey of Hepatitis C Virus Infection Among Apparently Healthy Individuals in Jos North, Plateau State, Nigeria - Frama, Ishaku; Zakka, Sheyin; Isa, Bigwan Emmanuel; Jiking, Gutau Fipo; Victoria, Ishaya (Kwaghe International Journal of Sciences and Technology, 2025)
Hepatitis C virus (HCV) infection poses a persistent global public health challenge due to its high transmissibility, potential for chronic progression, and association with severe hepatic complications such as liver cirrhosis and hepatocellular carcinoma (HCC). Despite its clinical relevance, HCV remains underdiagnosed and underreported in Jos North, Plateau State, Nigeria, where asymptomatic carriers often remain unaware of their infection status. This study aimed to determine the seroprevalence of HCV among apparently healthy individuals in Jos North and to identify associated sociodemographic and behavioural risk factors. Ethical approval was obtained from the Plateau State Ministry of Health. A total of 180 eligible participants were recruited, and venous blood samples (5 mL) were collected aseptically from the antecubital vein. Anti-HCV antibodies were screened using rapid immunochromatographic assay kits (Labtrust, UK) and confirmed using ELISA kits (Qingdao Hightop Biotech, China). Sociodemographic and risk factor data were collected via structured questionnaires. Statistical analysis was conducted using IBM SPSS version 27, with significance set at p ≤ 0.05. Results showed a seroprevalence rate of 5.0% (9/180), with slightly higher prevalence in females (5.4%) than males (4.3%), although this difference was not statistically significant (p = 0.524). The age group 51–65 years exhibited the highest prevalence (7.5%), followed by those aged 41–50 years (6.3%), with no significant association between age and HCV positivity (p = 0.731). The findings underscore the presence of silent HCV infection in the population and call for expanded screening, public health education, and the implementation of free routine testing in government health facilities to mitigate transmission and late-stage complications.